Marketing Innovation Linking Digital Marketing, Strategy, and MSME Performance in Jakarta - Adittya Budiman; Yudi Supriadi (Research Horizon, 2026)
This study aims to examine the effects of digital marketing and marketing strategy on the marketing performance of MSMEs, while investigating whether marketing innovation mediates these relationships within a government-operated digital procurement platform. A quantitative explanatory research design was employed. Data were collected through a survey of 369 MSMEs actively registered on the E-order platform managed by the Jakarta Provincial Procurement Service Agency. The data were analyzed using SmartPLS 4 to assess both direct and indirect relationships among the constructs. The findings reveal that digital marketing has a positive and significant effect on marketing innovation and marketing performance. Marketing strategy also shows a strong and significant direct influence on marketing performance and emerges as the most dominant determinant. However, marketing innovation does not significantly affect marketing performance and does not mediate the relationships between digital marketing, marketing strategy, and marketing performance. The results suggest that, within institutionally regulated digital procurement environments, MSME marketing performance is driven primarily by direct strategic execution and effective utilization of digital marketing capabilities rather than innovation-based mechanisms. These findings provide practical insights for MSME managers and policymakers in designing more effective digital marketing and strategic support programs.